Intercropping - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Benefits: - Crop yields increase, total farm output is generally raised and varies less from year to year. - Harvests are spread, extending food supply over a longer period. - A variety of food is produced reducing the risk faced by farmers who...